Strength and conditioning for wheelchair basketball: A narrative review - Yang, Y.; Johnson, Q. R.; Cabarkapa, D.; Fry, A. C. (International Journal of Sports Science and Coaching, 2026)
Adaptive sports are for individuals with disabilities, such as spinal cord injuries, with wheelchair basketball (WB) being one of the most popular globally. Although a strength and conditioning program is a fundamental component of athlete development in nondisabled sports, this approach is not as well implemented in WB. Several key components are necessary for strength and conditioning coaches working with WB athletes to improve health and athletic performance. These include the implementation of athlete needs analyses (e.g., energy system, biomechanical, competition demands, health and injury prevention), body composition, nutritional intake analysis, and the management of training loads. The goal of this narrative review was to compile scientific evidence and comprehensive information regarding the critical components that assist coaches in developing training programs for WB athletes. Furthermore, although WB athletes may not be able to utilize strength and conditioning training regimes designed for nondisabled athletes owing to their preexisting conditions, these training regimes (e.g., traditional weight training exercises) can still be implemented with modifications. A well-rounded strength and conditioning program will provide the necessary foundation for WB athletes' need for optimal performance in sports.